Dynamics of Ring Disclinations Driven by Active Nematic Shells - Hardoüin, Jérôme; Guillamat, Pau; Sagués, Francesc; Ignés-Mullol, Jordi (Frontiers in Physics, 2019)
When dispersed in thermotropic nematic liquid crystal oils, surfactant-ladden aqueous droplets often lead to the formation of a equatorial ring disclination in the nearby nematic matrix as a result of a balance between elasticity and interfacial energy. In this experimental work, the aqueous phase contains an extract of cytoskeletal proteins that self-assemble into an active quasi-two-dimensional shell featuring self-sustained periodic flows. The ensuing hydrodynamic coupling drives the surrounding liquid crystal and triggers oscillations in the disclinations. We describe the dynamic modes of the disclinations under different driving conditions, and explore their pathway to collapse under flow conditions.